(untitled) (Journal of Education and Development, 2022)
Business schools continue to monitor student perceptions of their curriculum during the ongoing pandemic. 274 graduating business seniors filled out a Spring 2022 exit survey asking their perceptions about the business school’s curriculum improving their abilities on twelve goals. A factor analysis of these twelve individual items resulted in keeping all items and creating three smaller scales (items/scale): Business Problem Solving (6 items), Presentation Skills (3 items) and Team-related Skills (3 items). These three scales were found to be reliable and sufficiently distinct from each other. Overall, students perceived that the business school’s curriculum improved their team-related skills significantly more than business problem solving and presentation skills. Grade Point Average or gender were not related to any scale improvement differences. Paired t-test results included finding that transfer students indicated significantly higher improvement on business problem solving and team-related skills than non-transfer students. In addition, non-quantitative majors showed higher improvement on presentation skills than quantitative majors. A stronger baseline for these three curriculum improvement scales has now been established for follow-up monitoring. Results are further discussed.